Choledochal cysts in children: Intrahepatic ductal dilatation does not indicate true intrahepatic biliary duct disease - Gezer, Hasan Özkan; Oğuzkurt, Pelin; Temiz, Abdulkerim; İnce, Emine; Ezer, Semire Serin; Hiçsönmez, Akgün (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Choledochal cysts (CCs) are rare abnormalities of the biliary tract. Presenting our clinical experience with CCs herein, we aimed to identify if intrahepatic ductal dilatation indicates true intrahepatic biliary duct disease. Materials and Methods: We retrospectively reviewed all cases of CCs in children diagnosed at a single center (Başkent University Faculty of Medicine, Department of Pediatric Surgery) institution from 2005 to 2015. Results: Of 18 patients with CCs, 7 were males (39%). The age range was 3 months to 17 years (mean age, 6.2±3.8 years). Intrahepatic bile duct dilatation was detected in 13 (72%) patients by preoperative scanning. Type I, II, III, and IVA cysts were diagnosed in 13, 1, 1, and 3 patients, respectively. In all patients, total cyst excision and Roux-en-Y hepaticoenterostomy were performed. Conclusion: In this study, most intrahepatic ductal dilatations seen on preoperative imaging were thought to be caused by a distal obstruction, not true intrahepatic biliary duct disease. This study supports the hypothesis that preoperatively distinguishing between type I and type IVA CCs is not necessary; it does not affect the initial treatment. We consider that complete cyst excision with Roux-en-Y hepaticojejunostomy is safe and should be performed soon after diagnosis, irrespective of symptom severity to avoid future complications.